Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Pemerintah pada Kabupaten/Kota di Provinsi Jawa Timur - Prasetyo, Aditya Dwi; Sudaryanti, Dwiyani; Hariri, Hariri (Universitas Islam Malang, 2024)
Finding out how regional original revenue, capital spending, and balancing funds affect regional governments' financial performance is the main goal of this study. This study's sampling strategy is based on documenting relevant information in various forms (e.g., notes, books, transcripts, etc.). There were 38 samples used to analyst the secondary data that was acquired from the official BPK RI website. The procedure makes use of SPSS 26 to do multiple linear regression analysis. According to this study's findings, regional governments in East Java Province's districts and cities can improve their financial performance by increasing capital expenditures, decreasing local revenue, and increasing balancing funds.Keywords: Regional Original Income, Capital Expenditure, Balancing Fund, Financial Performance.